2021
DOI: 10.1136/rmdopen-2020-001505
|View full text |Cite
|
Sign up to set email alerts
|

Self-protection strategies and health behaviour in patients with inflammatory rheumatic diseases during the COVID-19 pandemic: results and predictors in more than 12 000 patients with inflammatory rheumatic diseases followed in the Danish DANBIO registry

Abstract: AimsIn Danish patients with inflammatory rheumatic diseases to explore self-protection strategies and health behaviour including adherence to disease-modifying antirheumatic treatment (DMARD) during the initial phase of the COVID-19 pandemic and again after the reopening of the society started. Furthermore, to identify characteristics of patients with high levels of anxiety and self-isolation.MethodsPatients in routine care followed prospectively in the nationwide DANBIO registry were invited to answer an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 23 publications
4
71
0
4
Order By: Relevance
“…So far, few studies have assessed the impact of the COVID-19 pandemic on medication adherence in patients with rheumatic and respiratory diseases. In these studies, adherence was measured with self-report and results were conflicting, with some studies reporting a negative effect, and some reporting no effect [33][34][35][36][37]. One study analysed controller inhaler use in asthma and chronic obstructive pulmonary disease patients whose devices were electronically tracked and who received an alert for missed doses [38].…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have assessed the impact of the COVID-19 pandemic on medication adherence in patients with rheumatic and respiratory diseases. In these studies, adherence was measured with self-report and results were conflicting, with some studies reporting a negative effect, and some reporting no effect [33][34][35][36][37]. One study analysed controller inhaler use in asthma and chronic obstructive pulmonary disease patients whose devices were electronically tracked and who received an alert for missed doses [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of individuals included in the inflammatory rheumatoid disease registry had a participation rate of 35%. 14 Another study about seeking health care outside of regular clinical hours reported a participation rate of 36% for the random sample. 15 When examining their response rate by age groups, the response rate for individuals aged 50 to 59 years was the same as ours (44%), whereas, for individuals aged 30 to 39 years, it was lower than ours (23% versus 40%).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the authors of that global survey also found that changes in healthcare services for health issues other than COVID-19 had moderate or severe effects on patients since the COVID-19 outbreak (Chudasama et al, 2020). Worry about contracting COVID-19 was high amongst people with arthritis, with a higher proportion of self-isolation amongst people who have arthritis due to their condition compared to others their age (Glintborg et al, 2021). In our experience, some of the MEDRA and PIPPRA participants' hesitancy and COVID-19 fear around engaging in clinical research was influenced by family members, including adult children.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%